Revision Of The Tni Law And Limitations On Military Involvement In Civil Affairs: The Perspective Of Constitutional Supremacy - Ayik Christina Efata; Deny; Johannes Triestanto; Rio Akmal Syahbana; Rusdi Sanmas (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The 2025 amendment to the Law on the Indonesian National Armed Forces (TNI Law) represents a significant phase in the evolution of civil–military relations in Indonesia, particularly with regard to the regulation of military involvement in civilian affairs. This article aims to examine the implications of the amended TNI Law for the principles of constitutional supremacy and civilian supremacy within the framework of a democratic state governed by the rule of law. The analysis primarily focuses on provisions concerning the appointment of active-duty military personnel to certain civilian positions and their compatibility with the principle of functional separation between the military domain and civilian governance. This study employs a normative juridical method, utilizing statutory and conceptual approaches, combined with qualitative analysis of legal norms, constitutional doctrines, and scholarly perspectives drawn from national academic journals The findings indicate that while the amendment seeks to normatively adapt the role of the TNI to contemporary security challenges, it simultaneously raises constitutional concerns regarding potential overlaps between civilian and military functions. Although the legislature emphasizes the existence of limitations and civilian oversight mechanisms, the provisions governing civilian positions accessible to active military personnel remain sufficiently broad to allow varied interpretations in practice. Such conditions may generate tension between the demands of national defense effectiveness and the principle of constitutional supremacy, which requires the military to operate under democratic civilian control. Accordingly, the amendment to the TNI Law must be critically assessed to ensure that it does not undermine the security sector reform paradigm established in the post-Reformasi era. This article underscores the importance of normative clarity, strengthened oversight mechanisms, and consistent legal implementation to ensure that military involvement in civilian affairs remains aligned with constitutional mandates and the principles of the rule of law.